The Valuation of Bank Capital Adequacy from the Regulatory Perspective - Staškevičius, Juozapas Audvydas; Jočienė, Aldona (Ekonomika, 1999)
The effective supervision of banking institutions is the essential component of a strong economic environment. Banking supervision is a dynamic function, which reacts to the changes in the market, constantly reevaluats supervisory policy taking into consideration new trends and developments. One of the prudential requirements used by banking supervisors is Basle Committee proposed capital adequacy ratio. The methodology of calculating this ration has been strongly criticized by economists and bankers. It is predicted that this methodology will be replaced by contemporary capital adequacy measuring models: Value at Risk, “Building Block”, Empirical Simulation, Monte Carlo Simulation Methods.The authors of the article suggest to supplement methodology of capital adequacy calculation in Lithuanian regulatory system.